Challenges and Strategies in Translating Humour for Arabic Subtitling - Eljazouli, Abderrahim; Azmi , Noureddine (International Journal of Language and Literary Studies, 2024)
The translation of humour in audiovisual media presents unique challenges due to its cultural relativity and dependence on social, linguistic, and cultural contexts. While Audiovisual Translation (AVT) studies have expanded since their emergence in the 1950s, research on humour translation between English and Arabic remains understudied, particularly regarding culturally sensitive content. This study addresses this gap by examining the strategies employed in translating humorous content from English to Arabic in subtitled media. Using a corpus-based approach, this research combines qualitative and quantitative methodologies to analyze translation strategies for humour, with particular attention to sensitive topics including sex, religion, and politics. The qualitative analysis examines the specific challenges and solutions in translating culturally-bound humour, while the quantitative component provides statistical data on the frequency and distribution of various translation strategies. The findings reveal that Arabic subtitlers predominantly employ Preservation strategies (50%), followed by Reduction (18.2%) and Expansion (16.7%). This pattern differs from previous studies of other language pairs, suggesting that the English-Arabic translation of humour involves unique considerations and approaches. The research contributes to AVT scholarship by providing empirical evidence of translation strategies in the understudied English-Arabic language pair and offering insights into the handling of culturally sensitive humour in Arabic subtitling practices.